Modifiable Risk Factors for Dementia in Indonesia's Urban Population - Muhammad Khifzhon Azwar; Siti Setiati (Interna Publishing, 2021)
Background: Indonesia is one of ten countries in the world with estimated number of dementia case exceeding a million. The number of elderly population living in Indonesian cities has exceeded the number in rural areas, but the country lacks data representing the urban population better related to modifiable risk factors for dementia, prevention of which is crucial. We aimed to identify the modifiable risk factors for dementia in Indonesia's urban population. Methods: this case-control study used five-year data in Indonesia's national general hospital by tracing back medical record books of individuals aged 60 years and above in geriatric medicine outpatient clinic to the first hospital visit. Statistical analyses included bivariate and multivariate analyses to adjust for confounding factors appropriately. Results: data from 345 patients suggested that the significant risk factors for dementia were history of smoking (adjusted OR 2.860, 95% CI 1.559-5.246), history of hearing loss (adjusted OR 7.962, 95% CI 3.534-17.941), history of depression (adjusted OR 12.473, 95% CI 2.533-61.417), hypertension (adjusted OR 1.751, 95% CI 1.006-3.048), and diabetes mellitus (adjusted OR 2.561, 95% CI 1.482-4.425). Dementia patients had longer median duration of diabetes mellitus (12 years) than elderly without dementia (9 years) before the diagnosis of dementia. Single point late-life underweight condition and low educational attainment were not associated with dementia in Indonesia's urban setting. The risk factors for vascular dementia were largely similar to those of dementia. Conclusion: in Indonesian urban population, history of smoking, hearing loss, depression, hypertension, and diabetes mellitus are associated with dementia.